Supporting Black Students Through Their Science, Engineering, and Medicine Career Journeys: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Increasing the number of Black men and Black women who enter the fields of science, engineering, and medicine (SEM) will benefit the social and economic health of the nation. On May 2-3, 2022 the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine of the National Academies of Sciences, Engineering, and Medicine convened a workshop to highlight promising financial and supportive services and programs throughout various stages of career development. Sessions followed student progression through the major stages of education and career development, and identified policies and practices that aim to mitigate and alleviate long-standing barriers to the full participation of Black students in SEM at the K–12, undergraduate, and graduate and professional levels.
Keywords: Education

Measuring the Opportunity Gap for Children from Birth to Age Eight and Understanding Barriers to Access: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The Committee on Exploring the Opportunity Gap for Young Children from Birth to Age Eight is conducting a consensus study on the causes and consequences of the opportunity gap, which generally refers to the unequal or inequitable distribution of resources and opportunities on the basis of factors such as race, ethnicity, socioeconomic status, English proficiency, community wealth, geography, or familial situations. These gaps can contribute to or perpetuate inequities in well-being across groups of young children in a number of outcome domains. As part of its work, the committee held a virtual public information-gathering workshop on May 24, 2021. The purpose of the workshop was to inform the committee in its work, which will also draw on other public information-gathering sessions, peer-reviewed research, and commissioned papers from subject-matter experts, as well as the expertise of its members. This publication summarizes the presentation and discussion of the workshop.
Keywords: Behavioral and Social Sciences

Educational Pathways for Black Students in Science, Engineering, and Medicine: Exploring Barriers and Possible Interventions: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Academic preparation is critical to increase Black representation in Science, Engineering, and Medicine, but so, too, are such interrelated factors as providing mentoring and role models in sufficient numbers, adequately funding school and community support services, and analyzing the intentional and unintentional consequences of a range of policies and practices. To address these issues, the Roundtable on Black Men and Black Women of the National Academies of Sciences, Engineering, and Medicine convened a virtual workshop on September 2 and 3, 2020. Titled "Educational Pathways for Blacks in Science, Engineering, and Medicine: Exploring Barriers and Possible Interventions," the workshop provided a platform to explore challenges and opportunities, beginning in the earliest years of life through K-12 schooling, undergraduate and postgraduate education, and into the workforce. Presenters throughout the workshop provided perspectives from research and from their own experiences to discuss the need for systemic solutions inside and outside of formal education institutions. This publication summarizes the presentation and discussion of the workshop.
Keywords: Education

Closing the Opportunity Gap for Young Children - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Many young children in the United States are thriving and have access to the conditions and resources they need to grow up healthy. However, a substantial number of young children face more challenging conditions such as: poverty; food insecurity; exposure to violence; and inadequate access to health care, well-funded quality schools, and mental health care. In many cases, the historical origins of unequal access to crucial supports for children's physical, emotional, and cognitive development are rooted in policies that intentionally segregated and limited various populations' access to resources and create opportunity gaps that intertwine and compound to affect academic, health, and economic outcomes over an individual's life course and across generations. Closing the Opportunity Gap for Young Children, identifies and describes the causes, costs, and effects of the opportunity gap in young children and explores how disparities in access to quality educational experiences, health care, and positive developmental experiences from birth through age eight intersect with key academic, health, and economic outcomes. The report identifies drivers of these gaps in three key domains—education, mental health, and physical health—and offers recommendations for policy makers for addressing these gaps so that all children in the United States have the opportunity to thrive. In addition, the report offers a detailed set of recommendations for policy makers, practitioners, community organizations, and philanthropic organizations to reduce opportunity gaps in education, health, and social-emotional development.
Keywords: Behavioral and Social Sciences

Psychological Factors That Contribute to the Dearth of Black Students in Science, Engineering, and Medicine: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Efforts over the last several decades to increase the participation and leadership of Black men and women in the scientific and medical workforce have had limited results. Despite many individual successes, the number of Black professionals in science, engineering, and medicine (SEM) fields has not reached a level that corresponds with African American representation in the country at large. Structural racism affects progress at all stages along the pathway - from young children through graduate and medical students through faculty and clinicians at all levels. Beyond entry into educational programs or recruitment into workplaces seeking to diversify, challenges persist to achieve equity and inclusion for Black males and females. Moreover, psychological barriers confound the engagement of Black men and women in SEM fields. To explore these issues and suggest solutions, the National Academies of Sciences, Engineering, and Medicine launched the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine. Over the past 2 years, the Roundtable has convened workshops on K-12 education, the impact of COVID-19, financial burdens to pursuing SEM careers, and other topics. Sessions during each of these workshops identified psychological factors related to those specific topics. To have a more targeted discussion, the Roundtable convened a virtual workshop on September 14-15, 2021. As summarized in this proceedings, panelists and participants identified policies and practices that perpetuate these factors and explored solutions toward achieving and maintaining wellness, especially among students and young professionals.
Keywords: Education; Health and Medicine

Addressing Diversity, Equity, Inclusion, and Anti-Racism in 21st Century STEMM Organizations: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The National Academies of Sciences, Engineering, and Medicine's Committee on Addressing Diversity, Equity, Inclusion, and Anti-Racism in 21st Century STEMM Organizations convened a national summit in July 2021 that highlighted how racism operates at different levels in science, technology, engineering, mathematics, and medicine (STEMM) settings; reviewed policies and practices for confronting systemic racism; and explored ways to advance diversity, equity, and inclusion in STEMM settings. The 2-day, public webcast summit explored the empirical and experiential evidence related to the ways in which systemic racism and other barriers impede STEMM careers for historically marginalized racial/ethnic groups, and explored ways to address these barriers, including strategies undertaken by stakeholder communities. In this summit, speakers discussed how diversity, equity, inclusion, and anti-racism impact STEMM organizations. The workshop presentations focused on issues related to the history of racism in the United States, the lasting legacy of biased policies in the nation, and the research on practices to address systemic and structural racism in STEMM organizations. This publication summarizes the presentation and discussion of summit.
Keywords: Behavioral and Social Sciences

Understanding and Offsetting Financial Barriers for Black Students in Science, Engineering, and Medicine: Programs, Partnerships, and Pathways: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The number of Black students in science, engineering, and medicine in the United States has remained disproportionately low over the past several decades. A number of reasons have been identified as contributing to these low numbers, including those related to finances. Financial considerations range from the most immediate - the ability of students to pay for their education and associated costs - to more structural concerns, such as inequities that created and have perpetuated a wealth gap between races and ethnic groups. On April 19-20, 2021, the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine of the National Academies of Sciences, Engineering, and Medicine organized a virtual public workshop to examine financial barriers for Black students in science, engineering, and medicine, explore existing educational programs to them, and engage stakeholders in conversations about partnerships and policies that span academia, industry, and philanthropy. This publication summarizes the presentation and discussion of the workshop.
Keywords: Education

Reducing Inequalities Between Lesbian, Gay, Bisexual, Transgender, and Queer Adolescents and Cisgender, Heterosexual Adolescents: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
To better understand the inequalities facing lesbian, gay, bisexual, transgender, and queer (LGBTQ) youth and the promising interventions being used to address these inequalities, the National Academies of Sciences, Engineering, and Medicine's Board on Children, Youth, and Families hosted a virtual public workshop titled Reducing Inequalities Between LGBTQ Adolescents and Cisgender, Heterosexual Adolescents, which convened on August 25–27, 2021. The workshop was developed by a planning committee composed of experts from the fields of sociology, medicine, public health, psychology, social work, policy, and direct-service provision. This Proceedings of a Workshop summarizes the presentations and discussions from that workshop.
Keywords: Behavioral and Social Sciences

Building Educational Equity Indicator Systems: A Guidebook for States and School Districts - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
How can states and schools use data to support their efforts to improve educational equity? Building Educational Equity Indicator Systems: A Guidebook for States and School Districts, provides information to help state and school district leaders develop ways of tracking educational equity within their preK – 12 systems. The guidebook expands on the indicators of educational equity identified in the 2019 National Academies report, Monitoring Educational Equity, showing education leaders how they can measure educational equity within their states and school districts. Some of the indicators focus on student outcomes, such as kindergarten readiness or educational attainment, while others focus on student access to opportunities and resources, such as effective instruction and rigorous curriculum. Together, the indicators provide a robust picture of the outcomes and opportunities that are central to educational equity from preK through grade 12. For each indicator of educational equity identified in the report, the guidebook describes what leaders should measure and what data to use, provides examples of data collection instruments, and offers considerations and challenges to keep in mind. The guidebook is meant to help education leaders catalogue data they already collect and identify new data sources to help them fill gaps.
Keywords: Education; Behavioral and Social Sciences

The State of Anti-Black Racism in the United States: Reflections and Solutions from the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The mission of the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine at the National Academies of Sciences, Engineering, and Medicine is to advance discussions on the barriers and opportunities encountered by Black students and professionals as they navigate the pathways from K-12 and postsecondary education to careers in science, engineering, and medicine (SEM) and highlight promising practices for increasing the representation, retention, and inclusiveness of Black men and Black women in SEM. This proceedings serves as a summary of the presentations and discussions from a capstone workshop, held virtually on December 6 and 7, 2021, to review how anti-Black racism had permeated across the topics covered by the Roundtable over the previous 2 years.
Keywords: Policy for Science and Technology

Addressing the Drivers of Criminal Justice Involvement to Advance Racial Equity: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The Committee on Reducing Racial Inequalities in the Criminal Justice System of the National Academies of Sciences, Engineering, and Medicine convened a workshop in March 2021 as part of its exploration of ways to reduce racial inequalities in criminal justice outcomes in the United States. This workshop, the second in a series of three, enabled the committee to gather information from a diverse set of stakeholders and experts to inform the consensus study process. Speakers discussed the numerous interrelated factors that shape racial inequalities in the criminal justice system. Presentations focused on issues and promising solutions in health and well-being, in both neighborhood and opportunity contexts, as well as in youth-serving systems, as they relate to reducing racial inequality. This publication highlights the presentations of the workshop.
Keywords: Behavioral and Social Sciences

Reducing Racial Inequalities in Criminal Justice: Data, Courts, and Systems of Supervision: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The Committee on Reducing Racial Inequalities in the Criminal Justice System of the National Academies of Sciences, Engineering, and Medicine convened a workshop in April 2021 as part of its exploration of ways to reduce racial inequalities in criminal justice outcomes in the United States. This workshop, the third in a series of three, enabled the committee to gather information from a diverse set of stakeholders and experts to inform the consensus study process. Speakers at the workshop presented on deeply rooted inequalities within the criminal justice system, which exist not only in readily measured areas such as incarceration, but also in a much larger footprint that includes contact with police, monetary sanctions, and surveillance and supervision. This publication highlights the presentations and discussion of the workshop.
Keywords: Behavioral and Social Sciences

Addressing the Long-Term Effects of the COVID-19 Pandemic on Children and Families - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The COVID-19 pandemic has had an unprecedented impact on the lives of children and their families, who have faced innumerable challenges such as illness and death; school closures; social isolation; financial hardship; food insecurity; deleterious mental health effects; and difficulties accessing health care. In almost every outcome related to social, emotional, behavioral, educational, mental, physical, and economic health and well-being, families identifying as Black, Latino, and Native American, and those with low incomes, have disproportionately borne the brunt of the negative effects of the pandemic. The effects of the COVID-19 pandemic on children and families will be felt for years to come. While these long-term effects are unknown, they are likely to have particularly significant implications for children and families from racially and ethnically minoritized communities and with low incomes. Addressing the Long-Term Effects of the COVID-19 Pandemic on Children and Families identifies social, emotional, behavioral, educational, mental, physical, and economic effects of the COVID-19 pandemic and looks at strategies for addressing the challenges and obstacles that the pandemic introduced for children and families in marginalized communities. This report provides recommendations for programs, supports, and interventions to counteract the negative effects of the pandemic on child and family well-being and offers a path forward to recover from the harms of the pandemic, address inequities, and prepare for the future.
Keywords: Behavioral and Social Sciences

Transforming Trajectories for Women of Color in Tech - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Demand for tech professionals is expected to increase substantially over the next decade, and increasing the number of women of color in tech will be critical to building and maintaining a competitive workforce. Despite years of efforts to increase the diversity of the tech workforce, women of color have remained underrepresented, and the numbers of some groups of women of color have even declined. Even in cases where some groups of women of color may have higher levels of representation, data show that they still face significant systemic challenges in advancing to positions of leadership. Research evidence suggests that structural and social barriers in tech education, the tech workforce, and in venture capital investment disproportionately and negatively affect women of color. Transforming Trajectories for Women of Color in Tech uses current research as well as information obtained through four public information-gathering workshops to provide recommendations to a broad set of stakeholders within the tech ecosystem for increasing recruitment, retention, and advancement of women of color. This report identifies gaps in existing research that obscure the nature of challenges faced by women of color in tech, addresses systemic issues that negatively affect outcomes for women of color in tech, and provides guidance for transforming existing systems and implementing evidence-based policies and practices to increase the success of women of color in tech.
Keywords: Industry and Labor

Minority Serving Institutions: America's Underutilized Resource for Strengthening the STEM Workforce - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
There are over 20 million young people of color in the United States whose representation in STEM education pathways and in the STEM workforce is still far below their numbers in the general population. Their participation could help re-establish the United States' preeminence in STEM innovation and productivity, while also increasing the number of well-educated STEM workers. There are nearly 700 minority-serving institutions (MSIs) that provide pathways to STEM educational success and workforce readiness for millions of students of color—and do so in a mission-driven and intentional manner. They vary substantially in their origins, missions, student demographics, and levels of institutional selectivity. But in general, their service to the nation provides a gateway to higher education and the workforce, particularly for underrepresented students of color and those from low-income and first-generation to college backgrounds. The challenge for the nation is how to capitalize on the unique strengths and attributes of these institutions and to equip them with the resources, exceptional faculty talent, and vital infrastructure needed to educate and train an increasingly critical portion of current and future generations of scientists, engineers, and health professionals. Minority Serving Institutions examines the nation's MSIs and identifies promising programs and effective strategies that have the highest potential return on investment for the nation by increasing the quantity and quality MSI STEM graduates. This study also provides critical information and perspective about the importance of MSIs to other stakeholders in the nation's system of higher education and the organizations that support them.
Keywords: Education; Industry and Labor; Policy for Science and Technology

Advancing Antiracism, Diversity, Equity, and Inclusion in STEMM Organizations: Beyond Broadening Participation - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Individuals from minoritized racial and ethnic groups continue to face systemic barriers that impede their ability to access, persist, and thrive in science, technology, engineering, mathematics, and medicine (STEMM) higher education and workforce. Without actively dismantling policies and practices that disadvantage people from minoritized groups, STEMM organizations stand to lose much needed talent and innovation as well as the ideas that come from having a diverse workforce. A new report from the Board on Behavioral, Cognitive, and Sensory Sciences examines the backdrop of systemic racism in the United States that has harmed and continues to harm people from minoritized groups, which is critical for understanding the unequal representation in STEMM. The report outlines actions that top leaders and gatekeepers in STEMM organizations, such as presidents and chief executive officers, can take to foster a culture and climate of antiracism, diversity, equity, and inclusion that is genuinely accessible and supportive to all.
Keywords: Behavioral and Social Sciences

The Impacts of Racism and Bias on Black People Pursuing Careers in Science, Engineering, and Medicine: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Despite the changing demographics of the nation and a growing appreciation for diversity and inclusion as drivers of excellence in science, engineering, and medicine, Black Americans are severely underrepresented in these fields. Racism and bias are significant reasons for this disparity, with detrimental implications on individuals, health care organizations, and the nation as a whole. The Roundtable on Black Men and Black Women in Science, Engineering, and Medicine was launched at the National Academies of Sciences, Engineering, and Medicine in 2019 to identify key levers, drivers, and disruptors in government, industry, health care, and higher education where actions can have the most impact on increasing the participation of Black men and Black women in science, medicine, and engineering. On April 16, 2020, the Roundtable convened a workshop to explore the context for their work; to surface key issues and questions that the Roundtable should address in its initial phase; and to reach key stakeholders and constituents. This proceedings provides a record of the workshop.
Keywords: Behavioral and Social Sciences

Long-Term Impacts of COVID-19 on the Future Academic Careers of Women in STEM: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
On March 23-24, 2022, the National Academies of Sciences, Engineering, and Medicine held a virtual workshop to explore the long-term impact of COVID-19 on the future careers of women in STEM. Workshop participants represented multiple sectors (i.e., higher education, government, and non-profit) as well as various career paths and stages (e.g., assistant, associate, and full professors; graduate students; program officers; directors; and policy advisors). The two-day workshop convened experts and leaders to outline a national research agenda that ensures academic institutions and federal agencies are able to monitor and mitigate the long-term negative impacts of the pandemic on the career trajectories, job stability, and leadership roles of women - especially women of color — in STEM. This publication highlights the presentation and discussion of the workshop.
Keywords: Policy for Science and Technology

Suicide Prevention in Indigenous Communities: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Indigenous communities experience higher risks for suicide compared to the general U.S. population, with suicide as the second-leading cause of death among Indigenous children and young adults in North America. To reduce this trend, it is essential for prevention and intervention efforts to build on scientific evidence; cultural and local knowledge; and the best community, family, and institutional practices to reduce risk and increase protection. The Forum on Mental Health and Substance Use Disorders and the Forum for Children's Well-Being at the National Academies of Sciences, Engineering, and Medicine convened a three-part virtual public workshop on April 26, 2022, May 13, 2022, and June 10, 2022, to examine suicide risk and protective factors in Indigenous populations, discuss culturally appropriate and effective suicide prevention policies and programs, explore existing data systems and how data can be used for tracking suicide rates, and consider opportunities for action. This Proceedings highlights presentations and discussions from the workshop.
Keywords: Health and Medicine; Behavioral and Social Sciences

Structural Racism and Rigorous Models of Social Inequity: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Structural racism refers to the public and private policies, institutional practices, norms, and cultural representations that inherently create unequal freedom, opportunity, value, resources, advantage, restrictions, constraints, or disadvantage for individuals and populations according to their race and ethnicity both across the life course and between generations. Developing a research agenda on structural racism includes consideration of the historical and contemporary policies and other structural factors that explicitly or implicitly affect the health and well-being of individuals, families, and communities, as well as strategies to measure those factors. The Committee on Population of the National Academies of Sciences, Engineering, and Medicine convened a 2-day public workshop on May 16-17, 2022, to identify and discuss the mechanisms through which structural racism operates, with a particular emphasis on health and well-being; to develop an agenda for future research and data collection on structural racism; and to strengthen the evidence base for policy making. Speaker presentations and workshop discussions provided insights into known sources of structural racism and rigorous models of health inequity, revealed novel sources and approaches informed by other disciplines and related fields, and highlighted key research and data priorities for future work on structural racism and health inequity.
Keywords: Behavioral and Social Sciences